(untitled) (Academia Journal of Medicine, 2019)
Background: The traditional views of tick-borne rickettsioses as endemic diseases with largely focal distributions and limited host and geographic ranges, predetermined seasonality and defined tick associations became obsolete or at least very incomplete. This expansion of awareness about the existence of other rickettsial agents with varied clinical and epidemiological attributes has been thoroughly reviewed but it has presented new challenges to the medical and public health communities. Subjects and Methods: The clinical presentation and multiple organ dysfunctions in these patients were evaluated with a special focus on the renal manifestation and hepatic manifestations. The study population included all the patients presenting fever, rash and were diagnosed with rickettsial disease by clinical examination. A total of 60 subjects, satisfying the inclusion and exclusion criteria were included in the final analysis. The sample size was calculated assuming the expected proportion of rickettsial infection as 11% among fever cases as per previously published studies, with a precision of 8% and 95% confidence level. Results: The mean AST in the 80 titre was 140.43 ± 79.92, it was 285.89 ± 184.95 in 160 titre, 364.92 ± 89.69 in 320 titre group and 579.29 ± 106.26 in 640 titre group. The mean difference of AST 145.47 in 160 titre group was statistically significant (p value<0.001), 224.50 in 320 titre group was statistically significant (p value<0.001), and in 640 titre group 438.86 was statistically significant. (P- Value <0.001). Conclusion: The study has highlighted the need to have a high index of suspicion to enhance the diagnosis of ricketsial diseases and also the strong association between weilfelixtitre and liver and renal dysfunction.